Faktor-Faktor Penghambat Masyarakat Desa Tanjung Putus Untuk Bertransaksi di Bank Syariah - Siti Zumara,; Tuti Anggraini,; Nursantri Yanti, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Sharia banking experienced a very fast change of events and spread to various countries. The development of the process of making sharia banking products certainly raises concerns regarding the real factors that hinder Tanjung Putus Village residents from making transactions at sharia banks. So is it true that information factors, location factors, insight factors and brand factors can inspire people in Tanjung Putus Village to carry out transactions at sharia banks? So, to find out the factors that hinder the people of Tanjung Putus Village from carrying out transactions at sharia banks, factors related to buyer behavior were used. This examination aims to determine the elements that pressure the public to carry out transactions at sharia banks, especially the people of Tanjung Putus City. The type of research used in this research is quantitative research carried out with the help of the SPSS application and includes several testing stages, such as: hypothesis testing, multiple linear regression testing, normality testing, multicollinearity testing, and validity. Testing Looking at the results of the exploration that has been carried out, the results show that H0 is rejected and Ha is accepted, this means that the factors of information, area, wisdom and brand influence individual income in carrying out transactions at Sharia Commercial Banks.